Exploring Motifs In Towe Songke, Manggaraian Ethnic Woven Fabric, In Mathematics Perspective - Makur, Alberta Parinters; Gunur, Bedilius; Rampung, Bonefasius (SJME (Supremum Journal of Mathematics Education), 2020)
Connection between mathematical content and the cultures of learnersin mathematics education should be acknowledged and explored. Thisresearch, conducted using a qualitative research approach, withethnographic methods, explored the relationship between formalmathematics especially geometric patterns and Motifs of ManggaraiEthnic Woven Fabric, known as Towe Songke in Cibal, ManggaraiRegency, a rural area in East Nusa Tenggara Indonesia. Total 3weavers of the age ranging from 20 to 40 selected based on theirweaving knowledge and communication skills. Data were obtainedthrough interviews, observations, field notes, and documentations.The research resulted in how mathematics learning on subjects such as geometry and geometry transformation was associated with the local cultural context of Manggarai. This study identified the line symmetry and the effect of geometric transformations (translations,reflections, rotation, and reflection) of several motifs in Towe Songke. Most of motifs which are found in Towe Songke forms Frieze Pattern F7 because these motifs can be seen as translation, horizontal reflection, vertical reflection and half turn rotation symmetry.